2016
DOI: 10.1016/j.amjsurg.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of treatment strategies for severe splenic trauma in the pediatric population

Abstract: BACKGROUND Splenic angioembolization (SAE) is increasingly used in the management of splenic injuries in adults, although its value in pediatric trauma is unclear. We sought to assess outcomes related to splenectomy vs SAE. METHODS The National Trauma Data Bank was queried for patients 0 to 15 years of age from 2007 to 2011. Subgroup analysis of splenectomy vs SAE was performed for high-grade injuries using propensity analysis and inverse probability weighting. RESULTS Of 11,694 children presenting with sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 31 publications
2
7
0
2
Order By: Relevance
“…As shown in Table 2, tertiary centers had a higher percentage of patients with an ISS ≥ 16 than noncenter hospitals during every period of the study. These results are similar to the results of previous studies [11, 12]. The well-established infrastructure, facilities for immediate resuscitation and angiography, 24-h availability of the ICU and confidence of the trauma team might be influencing factors of this result [13].…”
Section: Discussionsupporting
confidence: 90%
“…As shown in Table 2, tertiary centers had a higher percentage of patients with an ISS ≥ 16 than noncenter hospitals during every period of the study. These results are similar to the results of previous studies [11, 12]. The well-established infrastructure, facilities for immediate resuscitation and angiography, 24-h availability of the ICU and confidence of the trauma team might be influencing factors of this result [13].…”
Section: Discussionsupporting
confidence: 90%
“…A primary concern in the case of patients with splenic injuries is the possibility of a delayed rupture after discharge. Based on the evidence, it was concluded that there is no difference between the survival rate in splenic trauma patients with surgical and non-surgical approaches (Rialon et al, 2016).…”
Section: Resultsmentioning
confidence: 99%
“…Prior success rates for NOM in the literature for pediatric patients are greater than 90% (14). A prior NTDB study published in 2016 noted a NOM success rate of 90%, with comparable morbidity and mortality rates between SAE and splenectomy in high-grade injuries (15). In addition, the association of NOM with improved clinical outcomes, such as LOS and fewer ICU days, is consistent with other studies showing NOM to be associated with a reduced blood transfusion, shorter LOS, or reduced mortality (16,17).…”
Section: Discussionmentioning
confidence: 99%